Integration of Project-Based Learning-STEM and Computational Thinking to Improve Students Scientific Creativity - Faradina; Ashari A. Usman; Sumarni Sahjad; Fitri Ayu Lestari; Fazrul M Yasin (IAIN Sorong, 2026)
Scientific creativity is one of the most essential aspects of 21st-century skills emphasized in science learning, as it enables students to generate scientific ideas that are original, flexible, and applicable in solving contextual problems. Therefore, this study aims to describe the implementation of Project-Based Learning (PjBL) integrated with STEM and Computational Thinking to enhance students’ scientific creativity.This study employed a quantitative approach with a pre-experimental method using a one-group pretest–posttest design. The sample consisted of 29 students from Class VIII-A at SMP Negeri 3 Ternate City. The research instruments included a scientific creativity test and an observation sheet to assess the implementation of the learning process. Data were analyzed using a paired sample t-test and N-Gain calculation to determine the improvement in students’ scientific creativity.The results showed that the implementation of the learning process reached 85%, which falls into the good category. In addition, the paired sample t-test results indicated a significance value of 0.000 < 0.05, demonstrating a significant difference between pretest and posttest scores. The average N-Gain score was 0.61, which is categorized as moderate. In conclusion, the implementation of Project-Based Learning (PjBL) integrated with STEM and Computational Thinking is associated with improvement of students’ scientific creativity.